ANALISIS PENGARUH UPAH MINIMUM PEKERJA DAN JUMLAH PENDUDUK MISKIN TERHADAP TINGKAT PENGANGGURAN DI SURABAYA - Ardyan, Putu Sardha; Sa`adah, Nuvi Wikhdatus (JEB17 : Jurnal Ekonomi dan Bisnis, 2016)
This study aimed to analyze the effect of the minimum wage and the number of poor workers on the unemployment rate in Surabaya at the time of the study from the year 2008-2012. The purpose of this study started from the author's observation on the unemployment rate in Surabaya from year to year changes, both the unemployment rate is likely to increase or vice versa is decreased. From the analysis of test data that the authors prove by analisisa correlation in saying that the relationship between the minimum wage and the number of poor people on the unemployment rate Based on our research and the estimates obtained from the test Regression with the results of TPT = 421 615 + - 0.174 UMP + - 0.777 TPT Based the results of parameter estimation equations open unemployment rate has explanatory power (Adjusted R-squared) of 0.887. From the table Fhitung 16.710 values obtained with a probability value (sig) = 0.043. Fhitung value (16.710)> F table (5.79) and Ttabel 2,015 <Thitung 4663 then H0 is rejected at the 5% significance level.Keywords : minimum wage workers, Period of Poor , Unemployment Rate